2011
DOI: 10.1186/1471-2377-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Types of the cerebral arterial circle (circle of Willis) in a Sri Lankan Population

Abstract: BackgroundThe variations of the circle of Willis (CW) are clinically important as patients with effective collateral circulations have a lower risk of transient ischemic attack and stroke than those with ineffective collaterals. The aim of the present cadaveric study was to investigate the anatomical variations of the CW and to compare the frequency of prevalence of the different variations with previous autopsy studies as variations in the anatomy of the CW as a whole have not been studied in the Indian subco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 18 publications
0
46
0
6
Order By: Relevance
“…The prevalence of the typical pattern of the CW has been reported to range from 14.00% to 45.20% in cadaveric examinations [4,11], in contrast to imaging studies where it has been observed in 22.29% to 45.76% [6,9] of the subjects. As shown in Table 5, the entire circle was reported to be open rather rarely -in 3.20% to 11.00% of the subjects [5,11].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The prevalence of the typical pattern of the CW has been reported to range from 14.00% to 45.20% in cadaveric examinations [4,11], in contrast to imaging studies where it has been observed in 22.29% to 45.76% [6,9] of the subjects. As shown in Table 5, the entire circle was reported to be open rather rarely -in 3.20% to 11.00% of the subjects [5,11].…”
Section: Discussionmentioning
confidence: 80%
“…Many authors have hypothesised that there are considerable differences in the prevalence of various configurations of the CW in various ethnic groups [4,11,13]. Conclusions based on the comparison of data acquired using different methods seem to be questionable.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations